Cladocolea molotensis (Loranthaceae), a new species for the cloud forest of Guerrero, Mexico - Martínez-Ambriz, Emmanuel; Lozada-Pérez, Lucio (Phytotaxa, 2016)
A new species of Cladocolea, belonging to the cloud forest from the region of the Costa Grande of Guerrero, Mexico, is described and illustrated. Cladocolea molotensis is morphologically similar to C. loniceroides, but it differs by the leaf base being rounded to obtuse, the presence of conspicuous calcium oxalate crystals in the leaf surface and the peduncle, the pistillate flowers being tetramerous or pentamerous, the petals glabrous and staminodes usually inconspicuous or absent in the pistillate flowers.